Selecting habitats to reintroduce the endangered species Ardisia gigantifolia (Primulaceae) based on growth and physiological traits - Rong Liu; Dan Xie; Mengling Li; Yanmei Ping; Dongmei Li; Shupeng Dong; Yongjie Yu; Jinguo Zhang; Zulin Ning (Global Ecology and Conservation)
Ardisia gigantifolia is a critically endangered medicinal plant endemic to China and only 77 wild individuals were found at present. To provide detailed information for selecting its restoration habitats, plantlets of this species were transplanted into four sites with different habitats, including two current sites (GLQ and HK) with extant populations, one historical site (NX) and one site (BG) outside its historical range but near the existing range. The survival, growth and physiological performance of transplanted plantlets and habitat characters were compared among the four sites, and the population structure and physiological traits of wild individuals were compared among the two extant populations. The results revealed that relative irradiance would be the main factor influencing the photosynthesis and growth of transplanted plantlets. Transplanted plantlets at NX presented the best overall performance in survival, growth and physiology, and presented better physiological performance than wild seedlings at the two current sites, revealing that NX was the optimal habitat for reintroduction of A. gigantifolia. Compared to NX, severe shading at GLQ and HK resulted in the decrease of light energy utilization efficiency and growth parameters. Wild seedlings at GLQ exhibited significantly lower light energy utilization efficiency but significantly higher malondialdehyde content than those at HK, which would explain the lower proportion of young individuals and the smaller growth trend in the GLQ population.